Probing an Interfacial Surface in the Cyanide Dihydratase from Bacillus pumilus, A Spiral Forming Nitrilase - Park, Jason M.; Mulelu, Andani; Sewell, B. Trevor; Benedik, Michael J. (Frontiers in Microbiology, 2016)
Nitrilases are of significant interest both due to their potential for industrial production of valuable products as well as degradation of hazardous nitrile-containing wastes. All known functional members of the nitrilase superfamily have an underlying dimer structure. The true nitrilases expand upon this basic dimer and form large spiral or helical homo-oligomers. The formation of this larger structure is linked to both the activity and substrate specificity of these nitrilases. The sequences of the spiral nitrilases differ from the non-spiral forming homologs by the presence of two insertion regions. Homology modeling suggests that these regions are responsible for associating the nitrilase dimers into the oligomer. Here we used cysteine scanning across these two regions, in the spiral forming nitrilase cyanide dihydratase from Bacillus pumilus (CynD), to identify residues altering the oligomeric state or activity of the nitrilase. Several mutations were found to cause changes to the size of the oligomer as well as reduction in activity. Additionally one mutation, R67C, caused a partial defect in oligomerization with the accumulation of smaller oligomer variants. These results support the hypothesis that these insertion regions contribute to the unique quaternary structure of the spiral microbial nitrilases.